Perilaku Hedonis Siswa dan Penanganannya - Amaliah amaliah; Abdul Saman (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
The research objective is to determine: 1) Description of students 'hedonic behaviour 2) Factors that cause hedonic behaviour 3) Efforts to handle students' hedonic behaviour. The research approach is qualitative with the type of case study research. The research subjects were two students. Data collection using interviews and observation guidelines. Data analysis using qualitative descriptive analysis. The results showed that 1) the US's hedonic behaviour was wearing branded clothes, shopping, hanging out in cafes, and hanging out with people of equal socio-economic level. In the subject of MT, hedonic behaviour is shown by living in a splurge, tending to choose branded goods, participating in shopping at famous clothing stores or distributions and hanging out only with friends who suit their interests. 2) Factors that influence AS and MT hedonic behaviour are divided into internal factors and external factors. Internal factors want to be recognized by the surrounding environment, self-actualization, self-existence, and hedonic behaviour perceptions. Meanwhile, external factors are the lack of family care, binding rules from the reference group and the social environment. 3) Handling hedonic behaviour using logotherapy shows a change in hedonic behaviour in both subjects. Handling on the subject is carried out by established procedures. Changes in AS and MT are changes in perspective, understanding of meaning, and behaviour aspects.